PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA KELAS VII SMP NEGERI 3 SINABOI TAHUN PELAJARAN 2015/2016 - Roma Yunita; Sriwulandari '; Suwondo ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is a research which is aimed to improve students biology studying achievement by implementing guided inqury learning srtategy in class VII SMP N 3 Sinaboi in Academic Year 2015/2016. This research was conducted in April-Mei 2016. The subject of this research was student of class VII of SMP N 3 Sinaboi. The number of students was 36 students (18 boys and 18 girls). The Parameter was students studying achievement consisted of comprehension ability, students passing individually, studens activities and teachers activities. The average of students comprehension ability in cycle 1 was 75.81% (moderate) increased became 81.42% (good). The students passing studying in cycle 1 was 63.88% (pass) increased in cycle 2 became 83.33% (pass). Average of studens activities in cycle 1 was 78.12% (moderate) increased in cycle 2 became 91.66% (very good). Average of teachers activities in cycle 1 was 88.45% (good) increased in cycle 2 became 92.30% (good). From the result of this research it can be concluded that the implementation of guided inquiry can improve students biology studying achievements in class VII SMP N 3 Sinaboi in Academic Year 2015/2016.Key Words: Guided Inquiry, Biology studying achiement